Caribbean Report 11-05-1993 - The British Broadcasting Corporation; Jarvis, Mike (anchor); Nicholls, Neville (interviewee); Compton, John (interviewee); Ali, Asgar (interviewee); Richardson, Richie (interviewee); Croskill, Hugh (correspondent); Alexis, Francis (interviewee); Bennendijk, Chandra van (correspondent) (The British Broadcasting Corporation, 1993)
St Lucian police officers could be sent to Haiti if a US proposal to deploy an international police force is accepted by the UN John Compton, St. Lucian Prime Minister gave that commitment. In Suriname local radio stations went off the air after an arson attack over a bitter dispute about who should be chief of the army. At the international whaling commission meeting in Japan – four Caribbean IWC members have sided with Japan, Norway, Chili and North Korea to vote against the establishment of the whale sanctuary in Antarctica. St Lucia and Guyana are calling on the international donor community to pay more attention to the region’s economic problems. Guyana’s Finance Minister - Asgar Ali said that he was expecting a more generous debt write off by the Paris club than what was announced. West Indies Captain Richie Richardson made his debut for English County team- Yorkshire. Richardson. Richardson speaks about his new role in this new club contract from a well-attended press conference. Senior police officers in Trinidad and Tobago have joined their junior counterparts in support of their embattled commissioner Jules Bernard – the police commission wants him to retire; he has been cited with not being cooperative with a Scotland Yard investigation.Hubert Alexander Ingraham, Bahamas Prime Minister says that he hopes that the Clinton administration will embrace free trade in the Caribbean, as well as Mexico. Headlines with anchor Mike Jarvis (00:32) 1. St Lucian police officers could be sent to Haiti if a US proposal to deploy an international police force is accepted by the UN John Compton, St. Lucian Prime Minister gave that commitment (00:33 -04:30) 2. In Suriname local radio stations went off the air after an arson attack over a bitter dispute about who should be chief of the army - Chandra Van Binnen Dyke reports (04:31 - 06:06) 3. At the international whaling commission meeting in Japan – four Caribbean IWC members have sided with Japan, Norway, Chili and North Korea to vote against the establishment ...